Negociações no processo de design: um estudo sobre a perspectiva do cliente na validação do projeto - Moraes, Daniela Sperb (Universidade do Vale do Rio dos Sinos, 2016)
The design process can take place between negotiations, conversations, exchanges of values and conflicts between client and designer. In these negotiations, the designer seeks to understand and meet the expectations of the actors involved in the network where the project is developed, aiming the acceptance of his proposals. Among these actors, it is understood that the client plays a key role in the acceptance the design process, because without the client approval, the artifact is unable to perform their roles in society. Identified such importance, the aim of this study is to understand the client perspective on the validation process in design. The term validate, that has meaning associated with "demonstrate the existence or truth of something by evidence" (MERRIAM-WEBSTER, 2014a), is used in different contexts in the field of Design. In this study, the use of the term comes from the idea of Krippendorff (2006), who explains that as the project is not an observable future, as in other areas, the designer needs to argue and convince stakeholders about the potential of his ideas to make them validate their proposals. To achieve the intended objective in the study, an exploratory survey was conducted, in which the data was collected through in-depth interviews with clients. Were considered "clients", the people responsible for making the approval of the design proposals in the furniture sector companies, located in Serra Gaucha region, and that normally hire outside firms to develop their artifacts. The results of the interviews were processed through Content Analysis and show some aspects present in the validation process: 1) heterogeneous groups composed of participants from different areas of organizations are formed for evaluation of new design proposals; 2) the validation does not occur at a specific time, but along the entire design process at different stages; 3) some aspects of the relationship between the client and the designer, as well as the reasons why the designer is hired can influence considerably in the project validation; 4) validation of a proposition is independent of the linearity of the design process of the designer; 5) The validation process occurs through a kind of coalescence, or by the combination of its components. The survey reached therefore an approximation of the reasons that make the client validate a proposition, expanding the theme validation in design and contributing to the theoretical and practical fields of this discipline.
Keywords: Validação no design; Relação cliente x designer; Design do produto; Indústria moveleira; Perspectiva do cliente; Validation in design; Relationship client x designer; Product design; Furniture industry; Client perspective; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial